The phylogeny of the tomato leaf mould fungus, Cladosporium fulvum syn. Fulvia fulva by analysis of rDNA sequences - Curtis, M.; Gore, J.; Oliver, Richard (1994)
The nucleotide sequence of part of the ribosomal DNA from races of the fungal tomato pathogen Cladosporium fulvum and other Cladosporium species have been determined. Comparisons of the internal transcribed spacer regions (ITS1 and ITS2) of several C. fulvum races showed complete sequence homology suggesting a recent evolutionary divergence. Comparisons of these nucleotide sequences in the ITS region with those of other Cladosporium species showed the close relationship within the Cladosporium genus. Using the nucleotide sequence of part of the 18s ribosomal subunit from these isolates and comparing them with sequences of some Ascomycetes, Basidiomycetes and Chytridiomycetes, obtained from GenBank, we infer the phylogeny of the Cladosporium species studied here. Our analysis shows that the Cladosporia form a monophyletic group which falls within the order Ascomycotina.